Surface waves in non-homogeneous, general magneto-thermo, viscoelastic media of higher order - Sethi, M.; Gupta, K.C.; Rani, M. (Zielona Góra: Uniwersytet Zielonogórski)
The aim of the present paper is to investigate surface waves in a non-homogeneous, isotropic, visco-elastic solid medium of n-th order including the time rate of strain. The theory of generalised surface waves has firstly been developed and then it has been employed to investigate particular cases of waves, viz., Stoneley, Rayleigh and Love type. The wave velocity equations have been obtained for different cases and are in well agreement with the corresponding classical result, when the effects of viscosity, temperature, magnetism as well as non-homogeneity of the material medium are ignored.
Keywords: inhomogeneous media; variable density; surface waves; viscosity